BRAF Immunoexpression Can Be Intralesionally Heterogeneous but BRAF V600E Mutation Status Is Intralesionally Homogeneous and Interlesionally Concordant in Melanoma: A Study of 140 Lesions From 98 Patients. (2nd July 2022) - Tachibana, Kota; Goto, Keisuke; Kukita, Yoji; Honma, Keiichiro; Isei, Taiki; Sugihara, Satoru; Taniguchi, Kohei; Yamasaki, Osamu
Abstract : Supplemental Digital Content is Available in the Text. Abstract: This study sought to confirm the homogeneity of BRAF V600E mutation status in melanoma. BRAF immunohistochemistry was performed on 102 lesions from 60 patients of melanoma with BRAF V600E mutation and 38 negative-control melanoma lesions from 38 patients, both of which were confirmed by real-time PCR or the MassARRAY System. In the positive-control lesions, 9 lesions from 7 patients with preceding BRAF-inhibitor therapy were included. Of the 102 BRAF -mutant lesions, 101 (99.0%) showed diffuse BRAF immunoexpression, but 39 (38.2%) of them showed various heterogeneous intensities. The heterogeneous intensity of immunostaining was due to necrosis ( n = 10), minimal or clear cytoplasm ( n = 5), tissue crush ( n = 8), insufficient fixation ( n = 24), or technical error ( n = 4). Only 1 lesion (1.0%) with nondiffuse immunoexpression harbored 80% weakly BRAF-positive tumor area and 20% BRAF-negative area with tissue damage. Sanger sequencing performed on the weak or negative regions in 7 lesions revealed BRAF V600E mutation in all the tested lesions. By contrast, all 38 negative-control lesions demonstrated no BRAF immunoexpression. This study demonstrated intralesional homogeneity and interlesional concordance for BRAF V600E mutation status and intralesional frequent heterogeneity for BRAF immunoexpression. The abovementioned 5 phenomena caused substantial reduction in BRAF immunostaining intensity. In 9 lesions within this study, BRAF immunoexpression and BRAF V600E point mutation status were not affected by preceding BRAF inhibitor therapy. Our data would also support the position that it does not matter whether we select primary or metastatic samples for BRAF mutation analysis.